Compressive behavior of concrete-filled ultra-high performance concrete tube with FRP stirrups. (December 2022) - Ding, Yi; Zhou, Zhen; Tian, Huiwen; Peng, Zhen
Abstract: Ultra-high performance concrete (UHPC) has excellent durability, compressive strength and toughness which can be combined with normal strength concrete (NSC) columns to improve the performance. In order to investigate the compressive behavior of concrete-filled UHPC tube, twelve circular composite columns with carbon fiber-reinforced polymer (CFRP) and glass fiber-reinforced polymer (GFRP) stirrups were tested. The effects of stirrup spacing and type on the axial behavior and failure mechanism of the composite columns were further analyzed. The research proved that the large-area spalling of the UHPC tube did not occur and the UHPC tube worked well with the internal concrete. Reducing the stirrup spacing and using the CFRP stirrups could significantly improve the ductility of specimens, but it had little influence on the initial stiffness. Then, a three-dimensional meso-scale model considering UHPC as two-phase material which composed of steel fibers and UHPC matrix was established. The simulated errors of the key mechanical performance indexes were almost within 15%, indicating that this finite element model could effectively reflect the compressive behavior of the concrete-filled UHPC tube columns. The influence rules of other variables including internal concrete strength, UHPC tube thickness and stirrup elastic modulus on the initial stiffness and peak load of specimens were also studied based on the validated model. Furthermore, the axial bearing capacity of the concrete-filled UHPC tube was predicted.